Viscoelastic computational modeling of the human head‐neck system: Eigenfrequencies and time‐dependent analysis - Boccia, E.; Gizzi, A.; Cherubini, C.; Nestola, M. G. C.; Filippi, S. (International journal for numerical methods in biomedical engineering, 2018)
A subject‐specific 3‐dimensional viscoelastic finite element model of the human head‐neck system is presented and investigated based on computed tomography and magnetic resonance biomedical images. Ad hoc imaging processing tools are developed for the reconstruction of the simulation domain geometry and the internal distribution of bone and soft tissues. Material viscoelastic properties are characterized point‐wise through an image‐based interpolating function used then for assigning the constitutive prescriptions of a heterogenous viscoelastic continuum model. The numerical study is conducted both for modal and time‐dependent analyses, compared with similar studies and validated against experimental evidences. Spatiotemporal analyses are performed upon different exponential swept‐sine wave–localized stimulations. The modeling approach proposes a generalized, patient‐specific investigation of sound wave transmission and attenuation within the human head‐neck system comprising skull and brain tissues. Model extensions and applications are finally discussed. A subject‐specific human head‐neck system is studied based on computed tomography and magnetic resonance dataset. Eigenfrequencies and time‐dependent analysis are performed via finite element method. Pixel‐based mechanical and viscoelastic properties are assigned.